Implementation of Social Security Protection for Workers at the Village Level (Research Study in Langsa-Aceh City) - Bustami Bustami; Rini Fitriani; Liza Agnesta Krisna (Journal of International Conference Proceedings (JICP), 2018)
The purpose of this study was to analyze the implementation of employment social security for workers at the village level through the Social Security Organizing Agency in Langsa-Aceh City. The type of research used is empirical juridical, the approach method used in this research is sociological juridical namely obtaining the truth empirically by directly reviewing the community towards the implementation of social security protection for workers at the village level. In reality the implementation of social security protection for workers at the village level has not run optimally, even though the social security contributions for the employment program are not taken from the salaries of the workers, but are funded by the government, there are 2 (two) obstacles which are internal policies of each -one of the village heads, and workers' lack of understanding of the rights to social security protection they have while externally is a lack of socialization from the Social Security Organizing Board so that misunderstandings of information received by the village head, and the election of new village heads are in the process. Efforts are made to improve socialization and provide detailed understanding to the village head about the objectives and benefits of the social security employment program for workers. Keywords: protection, social security, at the village level